“Symbolic Territories of Identity”, Geeks: Fantasy and Fiction Consumption in the Construction of Collective Identities in an Urban Tribe - Santos, Paulo Junio dos; Fagundes, André Francisco Alcântara; Medeiros, Cíntia Rodrigues de Oliveira (Organizações & Sociedade, 2022)
The aim of the present study is to investigate how the consumption of geek products acts in the identity of individuals who see themselves as members of this urban tribe. Geeks are taken as committed members fascinated by topics related to fantasy and science fiction universes; if we take into account a micro-scale, they form an identity territory. Based on its theoretical approach, the goal of the current research lies on promoting a dialogue between studies that have adopted the consumer culture theory (CCT) and organizational identity research, by taking into consideration that urban tribes are a kind of organization. The research corpus comprised interviews with seventeen people who identify themselves as geeks; these interviews were analyzed based on thematic categorization. Based on then results, geek-products’ consumption starts at childhood and goes all the way to adulthood; this process is influenced by characters in the fantasy and fiction universes. The consumed products hold symbolic elements of fantasy and fiction, so that they end up representing the extension of this tribe’s members ‘self’; moreover, they are a way of building collective identities within an urban tribe, in this case, geeks. We have shown that organizational identity studies can lead to greater dialogue with CCT in order to better understand complexities added to identity and multiple affiliations, and links in the identity construction of people forming an organization.